Identifying the temporal profiles of hedonic decline - Galak, Jeff; Kim, Jinwoo; Redden, Joseph P. (Organizational Behavior and Human Decision Processes, 2022)
The unfortunate reality of the human condition is that enjoyable experiences become less enjoyable with time and repetition. This hedonic decline has been well documented across a variety of stimuli and experiences. However, previous work has largely ignored the possibility that the temporal profile of hedonic decline varies at the individual level. In the present work, we first identify three temporal profiles of hedonic decline: flat, steady decline, and rapid onset decline. We next demonstrate that these temporal profiles of hedonic decline are relatively stable across both stimuli and time for any given individuals. That is, a temporal profile observed for one stimulus can be used to predict the temporal profile of hedonic decline for a novel stimulus or the same stimulus at a future date. We further explore the psychological underpinnings of these differences and note that Need for Cognition, a stable personality trait, partially explains which individuals will be more likely to experience different temporal profiles. Finally, we demonstrate two important downstream consequences to these three different temporal profiles of hedonic decline: re-consumption choice and re-consumption timing. This work provides a first look into the various ways in which hedonic decline operates at an individual level and documents predictable heterogeneity in such tendencies, an important departure from previous research looking at hedonic decline in aggregate.